Development and psychometric testing of the Spanish version of the Caregiver Preparedness Scale - Belen Gutierrez‐Baena; Carmen Romero‐Grimaldi (Wiley, 2021)
Abstract Aim To psychometrically test the Spanish version of the Caregiver Preparedness Scale (CPS) and document the preparedness level of caregivers. Design A descriptive and validation study. Method Purposive sampling method was used to select 171 family caregivers Spain. The scale was cross‐culturally adapted through a process that included translation, comparison with versions in other languages and back‐translation, review, pre‐testing and validity, and reliability tests. Results The Spanish family caregivers are mainly female (79%) and married (75%). The Spanish version of the CPS presents changes with respect to the original. Confirmatory factor analysis supported the single‐factor model. Analysis of internal consistency yielded a Cronbach's α of 0.89. Significant correlations (p < .01) with other scales supported convergent validity. A descriptive analysis of the validated scale showed average levels of preparation (2.16 out of 4). Caregivers felt better prepared to attend to the patient's physical needs than emotional or spiritual needs.